Esthetic soft tissue ridge augmentation around dental implant: Case report - Khalid S. Al-Hamdan (Elsevier, 2011)
The aim of this case report is to present a method to correct soft tissue ridge deformity around dental implant using acellular dermal matrix (ADM). A 25-year-old female patient presented with a missing maxillary first left premolar, which had class I soft tissue defect. The missing tooth was replaced with single implant supported prosthesis and the soft tissue defect was corrected using ADM utilizing the envelop technique. A 5-years follow-up is presented showing the long-term stability of this technique and the predictability of using the ADM as an alternative method to connective tissue graft to correct the soft tissue defect around dental implant. Keywords: Ridge defect, Alloderm, Ridge augmentation, Soft tissue esthetic